2011
DOI: 10.1177/0003319710394161
|View full text |Cite
|
Sign up to set email alerts
|

Coronary Artery Endothelial Dysfunction Associated With Sleep Apnea

Abstract: There is little information about coronary artery endothelial dysfunction in patients with sleep apnea. We evaluated relation between severity of sleep apnea and coronary artery endothelial dysfunction. In all, 26 patients without significant coronary stenoses were enrolled. Endothelial function was estimated by measuring coronary vasoreactivity in response to acetylcholine infusion (10(-7) mol/L) into coronary arteries. Vasoconstriction rate was defined as ([lumen diameter after isosorbide dinitrate injection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0
5

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 25 publications
1
8
0
5
Order By: Relevance
“…18 In individuals without significant coronary artery stenosis, coronary artery endothelial dysfunction (assessed as vasoconstriction rate by quantitative coronary angiography) is significantly associated with the severity of OSA. 19 One clinical manifestation of endothelial dysfunction is erectile dysfunction, which is present in the majority (69%) of sleep clinic populations with OSA. 20 In patients with acute MI, the prevalence of erectile dysfunction is significantly higher in those with versus without suspected OSA (74% vs 41%).…”
Section: Sdb and Endothelial Dysfunctionmentioning
confidence: 99%
“…18 In individuals without significant coronary artery stenosis, coronary artery endothelial dysfunction (assessed as vasoconstriction rate by quantitative coronary angiography) is significantly associated with the severity of OSA. 19 One clinical manifestation of endothelial dysfunction is erectile dysfunction, which is present in the majority (69%) of sleep clinic populations with OSA. 20 In patients with acute MI, the prevalence of erectile dysfunction is significantly higher in those with versus without suspected OSA (74% vs 41%).…”
Section: Sdb and Endothelial Dysfunctionmentioning
confidence: 99%
“…A specific coronary endothelial function has been scarcely studied in patients with OSA. Kadohira et al [26] reported a significant correlation between coronary endothelial dysfunction measured by vasoreactivity response to acetylcholine infusion and the severity of OSA. …”
Section: Pathophysiological Effects Of Osa In Cadmentioning
confidence: 99%
“…Repeated episodes of nocturnal hypoxemia result in endothelial dysfunction and remodeling of vascular walls, thus can lead to the development of systemic and pulmonary hypertension [14]. Moreover, the degree of OSAS severity, defined by AHI, has been found to correlate with the condition of coronary endothelial vessels and to affect their decongestion [15]. Our study revealed that the degree of OSAS correlated with an increase in TnT.…”
Section: Discussionmentioning
confidence: 53%